The Slovenian approach to talent identification and social inequality - Makarovič, Jan (Družboslovne razprave, 2000)
In his theory of elites' circulation, Pareto examined the relationship between the social and psychological inequality. During the rise to power of a new elite (understood as a group of especially talented individuals) these two inequalities become more congruent. On the other hand, when a new elite is well established, it often becomes opposed to the influx of new talent, so, the opposite tendency in the above relationship prevails. It goes without saying that social development is stimulated in the first case, and blocked in the second. The vicissitudes of the Slovenian system of identifying and stimulating talent that has developed since the late sixties, are discussed in the light of this theory.
Keywords: družbeno okolje; inteligentnost; nadarjenost; ustvarjalnost; družbena diferenciacija; družbena elita; Slovenia; Slovenija